Pembelajaran Luas Segitiga Menggunakan Ragam Bentuk Dengan Aktifitas Manipulasi - Cut Intan Salasiayah (Jurnal Kompetensi, 2012)
The width of triangle is usually taught by using right angled triangles. Many students are confused about how to determine the height of an obtuse triangle so that they cannot figure out the width of a triangle. In addition, the students usually memorize the formulas on the area of a triangle and the students find it difficult to explain ways to find out the formulas various forms of triangles. Learning atmosphere that promote activities done by the students is very important to build thorough knowledge. This learning starts from utilizing activities or concrete things, which gradually lead to the abstract ones. The area of a triangle can be taught in manipulation activities of known realistic things. Furthermore, various experiences are then needed for the concept of triangle’s width by using various forms of triangles such as right-angled triangle, equilateral triangle, isosceles triangle, scalene triangle.